PENYULUHAN APLIKASI FOTOGRAFI PRODUK PERTANIAN PADA KORPORASI PETANI DI DESA ADAT CITOREK KABUPATEN LEBAK - Fauzi, Muhammad; Hijrah Wicaksana, Harits (LPPM Universitas Bina Bangsa, 2025)
Social media and online marketplaces are used as marketing tools to boost the selling power of products and brands in the digital era. Product photos - especially agricultural products in the Citorek Traditional Village - are made using photography techniques to optimize marketing. These photos are then compiled and exhibited on social media and online marketplaces. Therefore, farmers and farm laborers in the Citorek Traditional Village need to improve their potential and skills. To overcome this problem, training, and counseling on the use of photography for agricultural products were carried out. The results obtained were that training and counseling activities on product photography applications for farmer corporations in the Citorek Traditional Village were carried out successfully, as evidenced by the enthusiasm and interest of the participants in this activity. Although some participants had difficulty practicing using DSLR cameras, they were still able to create high-quality product photos up to the editing stage (especially when using a Smartphone camera in Pro mode). After the activity was carried out, the evaluation that can be presented for future activities with this topic is digital marketing training and optimization of social media accounts and online marketplaces. This is to the needs expressed by farmers and farm laborers who participated in this activity.